Indiscreet - McCarey, Leo; Swanson, Gloria; De Sylva, Brown and Henderson; Feature Productions, Inc.; Cinetel Films ([Los Angeles, CA] : Feature Productions, 1931)
On New Year's Eve, Geraldine ('Jerry') Trent decides to break up with her boyfriend Jim Woodward, having finally grown tired of his dishonesty and his infidelities. Soon afterward, Geraldine meets and falls in love with novelist Anthony Blake. Blake knows that she has had a man in her past, but he is content as long as he never finds out who it was. All seems well until her sister Joan returns from a trip, and happily introduces Woodward as the new man in her life.
Originally released as a motion picture in 1931.
Gloria Swanson, Ben Lyon, Arthur Lake.
Cinematographers, Ray June, Gregg Toland; editor, Hal C. Kern; music and lyrics by B.G. DeSylva, Lew Brown and Ray Henderson.
In English.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed November 20, 2015).
Keywords: Women fashion designers -- Drama; Premarital sex -- Drama; Popular music -- United States -- 1931-1940.; Man-woman relationships -- Drama; Comedy films; Feature films; Internet videos; Streaming video